1997
DOI: 10.1161/01.hyp.30.5.1144
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, Hyperinsulinemia, and Blood Pressure

Abstract: In population surveys, blood pressure and plasma insulin concentration are related variables, but the association is confounded by age and obesity. Whether insulin resistance is independently associated with higher blood pressure in normal subjects is debated. We analyzed the database of the European Group for the Study of Insulin Resistance, made up of nondiabetic men and women from 20 centers, in whom insulin sensitivity was measured by the euglycemic insulin clamp. After excluding subjects aged > or =70 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(89 citation statements)
references
References 33 publications
4
76
0
9
Order By: Relevance
“…[15][16][17][18] Some investigators have reported that chronic administration of insulin might contribute to a sympathetically mediated increase in BP in animal models of obesity hypertension. 19,20 On the other hand, it has been reported that insulin administered acutely causes vasodilation and does not increase BP in animal or humans models.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Some investigators have reported that chronic administration of insulin might contribute to a sympathetically mediated increase in BP in animal models of obesity hypertension. 19,20 On the other hand, it has been reported that insulin administered acutely causes vasodilation and does not increase BP in animal or humans models.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The quantity and distribution of body fat is an important confounder in the insulin -BP relationship. 27,28 Although the positive association between IR and a high BP has been reported to be independent of obesity in some studies, 26,29 other studies have suggested that obesity, in particular central obesity, may be the cause of this association. 24,28,30,31 However, the present study showed that the level of IR, BMI and waist circumference were independent risk factors of a high BP in normoglycemic Koreans.…”
Section: Discussionmentioning
confidence: 99%
“…These include the evaluation of fasting glucose and insulin ratio, the analysis of glucose and insulin profiles after oral glucose load using 75 g dextrose (OGTT) and the so-called 'gold standard' method, which is the euglycemic hyperinsulinemic clamp technique. 21,22 Three indices were obtained using different procedures: (1) homeostasis model assessment (HOMA 23 ): fasting glucose (mmol l -1 )  fasting insulin (mU l -1 ); (2) Matsuda index of glucose and insulin profiles after OGTT: 24 10 000 OG0  I0x G mean  I mean , where G and I represent the plasma glucose (mg per 100 ml) and insulin (mU l -1 ) concentrations, respectively, expressing fasting (0) and mean OGTT concentrations; (3) euglycemic, hyperinsulinemic clamp technique (M-value) as described recently in the EU-RISC protocol: 19,25 Exogenous insulin is administered as a primed-continuous infusion at a rate sufficient to maintain a pre-set hyperinsulinemic plateau; simultaneously, the glucose concentration is clamped at the normal fasting level by means of an exogenous infusion of glucose. With this latter technique, the insulin action is measured in vivo under comparable conditions of stimulus (the plasma insulin concentration) and substrate (the plasma glucose concentration 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were obtained from a wrist vein heating the hand to 60 1C on a heating pad (for intermittent blood sampling of arterialized venous blood), for measurement of plasma and insulin concentrations. 25 …”
Section: Methodsmentioning
confidence: 99%